Long-lasting stress, burnout syndrome, aging, and risk of Alzheimer's Disease - Emilia Mikołajewska; Dariusz Mikołajewski (Kazimierz Wielki University, 2019)
Burnout is defined as an excessive stress reaction to environment characterized by emotional and physical exhaustion, coupled with a sense of frustration and failure. Work-related stress, especially low job control and low social support, may increase the risk of dementia, especially AD. Aim of the paper is a better understanding of the complex nature of th long-lasting stress and professional burnout to early symptoms of the AD onset. Identification of mechanisms underying of such associations may help to develop more effective therapeutic strategies better tailored to patient's profile. Despite efforts of scientists and clinicians objective diagnostic criteria and influence of burnout syndrome to AD remain ambiguous, making it difficult to recognize transition to early stage of AD. Additional longitudinal research is needed for determining what mediates the stress, burnout, and AD association, including both genders and not yet known risk factors.